2022
DOI: 10.3390/ijerph19148752
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution and the Health of Vulnerable Groups: A Systematic Review Focused on Particulate Matter (PM), Volatile Organic Compounds (VOCs) and Their Effects on Children and People with Pre-Existing Lung Disease

Abstract: Air pollution affects health, but much of the focus to this point has been on outdoor air. Higher indoor pollution is anticipated due to increasingly energy-efficient and less leaky buildings together with more indoor activities. Studies of indoor air pollution focusing on children and people with respiratory disease from the database Web of Science (1991–2021) were systemically reviewed according to the PRISMA guidelines, with 69 studies included in the final selection. Emissions from building materials affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…The interior environment of a house is contaminated by various gases and particles produced during various human activities such as cooking, smoking, burning, candles, insecticides, incense sticks, etc [10]. The current study discovered that poor indoor air quality has a significant association with respiratory illness.…”
Section: Discussionmentioning
confidence: 64%
“…The interior environment of a house is contaminated by various gases and particles produced during various human activities such as cooking, smoking, burning, candles, insecticides, incense sticks, etc [10]. The current study discovered that poor indoor air quality has a significant association with respiratory illness.…”
Section: Discussionmentioning
confidence: 64%
“…At indoor level, in order to improve people’s health conditions, we suggest increasing the ventilation rate in the work places and houses. Indeed, previous studies have shown how an improvement in indoor air given by better ventilation increases productivity and prevents pathological conditions such as rhinitis and the risk of allergic symptoms [ 24 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) in indoor air are believed to contribute to sick building syndrome and multiple chemical sensitivity (Win-Shwe et al, 2013;Redlich et al, 1997). They could also exacerbate asth-ma and chronic obstructive pulmonary disease (COPD) (Maung et al, 2022;Bentayeb et al, 2015). From 1997 through 2002, the Ministry of Health, Labour, and Welfare (MHLW) in Japan established indoor air guidelines to maintain public health for 13 VOCs and semi-volatile organic compounds, including aldehydes, alkanes, aromatic hydrocarbons, pesticides, and phthalates (MHLW, 2000a(MHLW, , 2000b(MHLW, , 2001(MHLW, , 2002.…”
Section: Introductionmentioning
confidence: 99%